Comparativo del rendimiento y calidad de nuevos cultivares de Caña de Azúcar (Saccharum officinarum) en la Estación Experimental Agraria “El Porvenir” – Juan Guerra - Valles Ramírez, Ayda Karín (2009)
In order to evaluate the agronomic behavior of the varieties of cane of sugar and to determine the variety or more promissory varieties with relationship to their yields and according to the conditions agrobioclimáticas of the study area, he/she was carried out the present experiment, likewise it was developed in the fields of the project cane of sugar of the E.E.A. “El Porvenir" that this located in the Km 14 of the highway Fernando Belaunde Terri, District of Juan Guerra. For such an effect the Design Blocks was used Totally at random, with 20 treatments and 4 repetitions. The results demonstrated that the treatments T2 (CP72-2086) and T20 (PCG12-745) they obtained the biggest yields with 133,72 and 130,66 t/ha, overcoming the witness T18 (H32-8560) that reached 128,94 t/ha. Likewise the treatment T5 (CP81-3058) with 339.50 cm it reached the biggest height in comparison with the other studied varieties, overcoming the witness T18 (H32-8560) that obtained 334,00 cm. on the other hand the treatment T3 (CP73-1547) with 3.15 cm he/she obtained the biggest shaft diameter, overcoming the witness T18 (H32-8560) that obtained 3,12 cm. The treatments that highlighted for the biggest entrenudos number they were the T19 (Mex73-523), T13 (CP82-1172) and T12 (CP72-1240) with 29,25, 28,84 and 27,25 knots respectively, overcoming the witness T18 (H32-8560) that reached 25.50 entrenudos. The biggest degrees brix obtained the treatments T9 (CP81-1254), T5 (CP81-3058) and T12 (CP72- 1240) with averages of 25,77, 24,43 and 24,26 degrees respectively.